ダイ4ジ ノ ナンキョク チイキ カンソク ニオケル ユウソウチュウ ノ テンキ ニツイテ - 久我, 雄四郎; クガ, ユウシロウ; KUGA, Yushiro (国立極地研究所, 1962)
P(論文) 1. Introduction The expedition ship "SOYA" was manned by three meterologists, who were in charge of weather forecasting for the operation as well as of regular ship surface observations and occasional radio-sonde observations. The weather analysis was made twice a day on the basis of the synoptic charts, 0600Z and 1800Z, which cover the whole southern hemisphere. This paper briefly reports the results of the analysis with respect to the area limitted between 40°W and 80°E. 2. Distinctive features of the synoptic pattern of this season a) A superior southward extension of subtropical anticylone was seen in January. b) The influence of the Antarctic continental anticyclone was predominant in middle December and in February. c) The change of weather phenomena in the vicinity of Lutzow-Holm Bay was considerably regular. d) There were two periods of conservative stable weather in the Antarctic coastal region, late December and early February. The former was caused by the southerly extension of subtropical anticyclone. 3. Cyclones The trajectories of major cyclones are shown in Figs. 1 and 2. Among these cyclones, two, which had developed in the area near Bouvet Island, approached Lutzow-Holm Bay, causing storms which attacked "SOYA" on Jan. 9 and 21. The relief operation was interrupted for a week or more before and after the storms. Another small depression, associated with the Antarctic front along the coast, hit Syowa Base on Jan. 31 giving minor effect on our operation. 4. Anticyclones a) Subtropical anticyclone. The quasistationary subtropical anticyclones, which are usually situated in the area between 20°S-45°S and 20°W-40°E, were developed so remarkably in middle January that their influence extended as far as to the Antarctic coast including Syowa Base, until the general pattern was changed by the approach of a deep trough at the end of middle January. b) Antarctic continental anticyclone. In middle December, Syowa Base and Lutzow-Holm Bay were under the control of the superior Antarctic continental ...